Assessment of the association between PM2.5 concentration and hospital admissions for pediatric asthma in Ho Chi Minh City, Viet Nam - Tinh Huu Ho; Chinh Van Dang; Thao Thi Bich Pham; Hien Thi Thu Ngo; Supat Wangwongwatana (Elsevier, 2024)
Despite the growing concern over the impact of ambient fine particulate matter (PM2.5) on respiratory health, studies on the association between PM2.5 and childhood asthma in Vietnam have remained relatively sparse.The study aimed to evaluate the short-term effects of PM2.5 on asthma hospital admissions in Ho Chi Minh City (HCMC), the most populous city in Vietnam. The PM2.5 database from 2016 to 2019 was collected at two fixed monitoring stations. The health database was collected from all three children's hospitals. A time-series regression analysis was conducted to examine the associations between the daily PM2.5 concentration and hospitalizations for asthma.A total of 11,223 records of children under five years old hospitalized for asthma were collected, of which 64 % were male and 70 % were aged 2 to under five years old. The daily mean PM2.5 concentration over the study period was 28.2 μg/m3. Each 10 μg/m3 increase in PM2.5 at lag2, lag3, and lag04, we found that the excess risk of total asthma hospital admission was 2.71 %, 2.63 %, and 3.9 %, respectively. According to the subgroup analysis, female gender and children aged from two to under five years had more significant effects.PM2.5 poses a risk to children's health; therefore, the local authority should prioritize improving the air quality.